Influence of PSRC1, CELSR2, and SORT1 Gene Polymorphisms on the Variability of Warfarin Dosage and Susceptibility to Cardiovascular Disease - AL-Eitan LN; Elsaqa BZ; Almasri AY; Aman HA; Khasawneh RH; Alghamdi MA (Dove Medical Press, 2020)
Laith N AL-Eitan,1 Barakat Z Elsaqa,2 Ayah Y Almasri,1 Hatem A Aman,1 Rame H Khasawneh,3 Mansour A Alghamdi4,5 1Department of Biotechnology and Genetic Engineering, Faculty of Science and Arts, Jordan University of Science and Technology, Irbid 22110, Jordan; 2Faculty of Medicine, Jordan University of Science and Technology, Irbid 22110, Jordan; 3Department of Hematopathology, King Hussein Medical Center (KHMC), Royal Medical Services (RMS), Amman 11118, Jordan; 4Department of Anatomy, College of Medicine, King Khalid University, Abha 61421, Saudi Arabi; 5Genomics and Personalized Medicine Unit, College of Medicine, King Khalid University, Abha 61421, Saudi ArabiaCorrespondence: Laith N AL-EitanDepartment of Biotechnology and Genetic Engineering, Faculty of Science and Arts, Jordan University of Science and Technology, P.O. Box 3030, Irbid 22110, JordanTel +962-2-7201000 ext 23464Email lneitan@just.edu.joBackground: Cardiovascular disease is one of the most common causes of morbidity and mortality worldwide. Several cardiovascular diseases require therapy with warfarin, an anticoagulant with large interindividual variability resulting in dosing difficulties. The selected genes and their polymorphisms have been implicated in several Genome-Wide Association Study (GWAS) to be associated with cardiovascular disease.Objective: The goal of this study is to discover if there are any associations between rs646776 of PSRC1, rs660240 and rs12740374 of CELSR2, and rs602633 of SORT1 to coronary heart disease (CHD) and warfarin dose variability in patients diagnosed with cardiovascular disease undergoing warfarin therapy.Methods: The study was directed at the Queen Alia Hospital Anticoagulation Clinic in Amman, Jordan. DNA was extracted and genotyped using the Mass ARRAY™ system, statistical analysis was done using SPSS.Results: The study found several associations between the selected SNPs with warfarin, but none with cardiovascular disease. All 4 studied SNPs were found to be correlated to warfarin sensitivity during the stabilization phase except rs602633 and with warfarin dose variability at the initiation phase. CELSR2 SNPs also showed association with dose variability during the stabilization phase. Also, rs646776 and rs12740374 were linked to warfarin sensitivity over the initiation phase. Only rs602633 was associated with INR treatment outcomes.Conclusion: The findings presented in this study found new pharmacogenomic associations for warfarin, that warrant further research in the field of genotype-guided warfarin dosing.Keywords: warfarin, SNPs, pharmacogenetics, Jordan